Cognitive reserve as an outcome predictor: first‐episode affective versus non‐affective psychosis. (14th August 2018) - Amoretti, S.; Cabrera, B.; Torrent, C.; Mezquida, G.; Lobo, A.; González‐Pinto, A.; Parellada, M.; Corripio, I.; Vieta, E.; de la Serna, E.; Butjosa, A.; Contreras, F.; et al.
Abstract : Objective: Cognitive reserve (CR) refers to the brain's capacity to cope with pathology in order to minimize the symptoms. CR is associated with different outcomes in severe mental illness. This study aimed to analyze the impact of CR according to the diagnosis of first‐episode affective or non‐affective psychosis (FEP). Method: A total of 247 FEP patients (211 non‐affective and 36 affective) and 205 healthy controls were enrolled. To assess CR, common proxies have been integrated (premorbid IQ; education–occupation; leisure activities). The groups were divided into high and low CR. Results: In non‐affective patients, those with high CR were older, had higher socioeconomic status (SES), shorter duration of untreated psychosis, and a later age of onset. They also showed greater performance in most cognitive domains. In affective patients, those with a greater CR showed a higher SES, better functioning, and greater verbal memory performance. Conclusion: CR plays a differential role in the outcome of psychoses according to the diagnosis. Specifically, in order to address the needs of non‐affective patients with low CR, cognitive rehabilitation treatments will need to be 'enriched' by adding pro‐cognitive pharmacological agents or using more sophisticated approaches. However, a functional remediation therapy may be of choice for those with an affective psychosis and low CR.